Factors Influencing Consumer Intention to Purchase Plant-Based Milk in Indonesia: An Exploratory Research - Richard Chandra; Dhiya Athaya Purwanti; Samuel Sebastian; Selia Evanny Pranata; Indria Handoko (Universitas Airlangga, 2022)
The consumption rate of plant-based milk has been increasing in recent years. This also suggests the decreasing trend of cow milk consumption, as the consumers shift to plant-based milk. This study aims to examine what factors influence the consumers’ intention to drink plant-based milk. For this purpose, the approach-avoidance theory was adopted to explore both facilitating (positive) and inhibiting (negative) factors that influence the consumers’ intention to consume the product. This study adopts qualitative research by interviewing 15 plant-based milk consumers and comparing them with 10 cow milk consumers about their perception of plant-based milk consumption. Indonesia was chosen as one large emerging economy in Southeast Asia with a tremendous consumption rate. The research findings suggest nine factors affecting consumers' intention in purchasing plant-based milk, namely: trends, price, sickness awareness, nutrition awareness, sensory, environmental concerns, packaging, brand, and ways to consume. Keywords: plant-based milk, consumer intention, qualitative research, Indonesia